Self-Reflection Model for English Teachers to Improve Teaching Competences - Paskalina Widiastuti Ratnaningsih (Indonesian Journal of English Language Studies (IJELS), 2015)
Reflection is an integral part of evaluation. It explores human being?s experiences of whathave been done. The aim of this research is to discover the conceptual model andtheempirical model of self-reflection model for English teachers. It is hoped that the Englishteachers be more efficient in teaching.Reflection is alsoable to dig out the transcendentmeaning of human experience. As a teacher, reflection is used in order to look back at theexperience in teaching in order to have better teaching for self-actualization. The teachersbecome aware of their experiences and do self-reflection. This project focuses on researchand development. The research results are the conceptual model adapted from two existingmodels and the empirical model of teacher?s self reflection which provides criteria ofteaching competences. They are pedagogy, personality, social, and professional competencesto reflect and integrated in 2013 curriculum. 2013 curriculum is used since it is the newestformal basis for teaching and learning. The teachers reflect their lived experience of thosecompetences for self-improvement and make progress of their teaching.Keywords: reflection, efficiency, self-actualization, English teachers, teaching competences,2013 Curriculum, self-improvement